NUANSA TASAWUF IMAM LAPEO DALAM KALINDAQDAQ MANDAR: KAJIAN HERMENEUTIKA - Zainuddin Hakim (Balai Bahasa Sulawesi Selatan, 2012)
This writing discusses about Mandar literary work, called kalindaqdaq especially kalindaqdaq which is much influenced by sight of Islamic mysticism literary. Islamic mysticism known widely in Mandar society is Imam Lapeo mysticism. It is analyzed using hermeneutic theory. The analysis aims at explaining two things, the meaning of word in line and of line in kalindaqdaq stanga (poetry), and mysticism shades in kalindaqdaq. The analysis is done using descriptive method and library research technique. The analysis shows that each stanga of kalindaqdaq poetry has unified meaning with the shades of Imam Lapeo mysticism. Abstrak Tulisan ini membahas karya sastra Mandar, yaitu kalindaqdaq khususnya kalindaqdaq yang mengandung wawasan sastra sufi atau tasawuf. Tasawuf yang dikenal luas di kalangan masyarakat Mandar adalah tasawuf Imam Lapeo. Data Tulisan ini dianalisis dengan teori hermeneutika. Tujuan kajian ini direalisasikan dalam dua hal, yakni makna kata dalam larik, dan larik dalam bait kalindaqdaq(puis'i) serta nuansa tasawuf Imam Lapeo dalam kalindaqdaq. Kajian dilakukan dengan metode deskriptif, dengan teknik kajian pustaka. Realitas kajian menyatakan bahwa setiap bait puisi kalindaqdaq memiliki makna yang utuh dengan nuansa tasawuf Imam Lapeo